Clinical safety and effectiveness evaluation of a new antimicrobial wound dressing designed to manage exudate, infection and biofilm - Metcalf, Daniel G (Int Wound J, 2016)
The objective of this work was to evaluate the safety and effectiveness of a next‐generation antimicrobial wound dressing (NGAD; AQUACEL (®) Ag+ Extra™ dressing) designed to manage exudate, infection and biofilm. Clinicians were requested to evaluate the NGAD within their standard protocol of care for up to 4 weeks, or as long as deemed clinically appropriate, in challenging wounds that were considered to be impeded by suspected biofilm or infection. Baseline information and post‐evaluation dressing safety and effectiveness data were recorded using standardised evaluation forms. This data included wound exudate levels, wound bed appearance including suspected biofilm, wound progression, skin health and dressing usage. A total of 112 wounds from 111 patients were included in the evaluations, with a median duration of 12 months, and biofilm was suspected in over half of all wounds (54%). After the introduction of the NGAD, exudate levels had shifted from predominantly high or moderate to low or moderate levels, while biofilm suspicion fell from 54% to 27% of wounds. Wound bed coverage by tissue type was generally shifted from sloughy or suspected biofilm towards predominantly granulation tissue after the inclusion of the NGAD. Stagnant (65%) and deteriorating wounds (27%) were shifted to improved (65%) or healed wounds (13%), while skin health was also reported to have improved in 63% of wounds. High levels of clinician satisfaction with the dressing effectiveness and change frequency were accompanied by a low number of dressing‐related adverse events (n = 3; 2·7%) and other negative observations or comments. This clinical user evaluation supports the growing body of evidence that the anti‐biofilm technology in the NGAD results in a safe and effective dressing for the management of a variety of challenging wound types.